Patient Safety in CT Imaging: Best Practices for Technologists (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Computed Tomography (CT) imaging is a vital diagnostic tool in modern medicine, but it carries inherent risks, including radiation exposure, contrast-related complications, and procedural errors. Radiologic technologists play a critical role in ensuring patient safety by adhering to best practices in protocol optimization, radiation dose reduction, patient screening, and emergency preparedness. This paper reviews key safety strategies, presents evidence-based recommendations, and provides actionable guidelines for technologists to minimize risks while maintaining diagnostic efficacy.